Analisis Potensi Kebangkrutan Pada PT Bank Central Asia Tbk dan PT Bank Negara Indonesia (Persero) Tbk Dengan Metode Altman Z-Score - Sarjono, Hendri (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
This study examines the bankruptcy potential of two major banks in Indonesia, namely PT. Bank Central Asia Tbk and PT. Bank Negara Indonesia (Persero) Tbk, using the Altman Z-Score method. The objective of this research is to assess the bankruptcy risk of both banks and to identify whether they fall into the safe or distress category. This research applies a quantitative method with a descriptive approach. The data used are secondary data obtained from the annual financial reports of both banks from 2011 to 2021, sourced from the Indonesia Stock Exchange official website and the banks' respective official websites. Data collection techniques include literature review and documentation study. The data analysis uses financial ratios, including Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), Earnings Before Interest and Taxes to Total Assets (X3), and Market Value of Equity to Total Liabilities (X4), which are then processed using the Altman Z-Score formula for non-manufacturing companies. The results show that throughout the observed period, both banks were categorized in the distress zone (potential bankruptcy) as their Z-scores remained below 1.81. These findings indicate a significant financial risk that should be seriously addressed by management. This study recommends further comprehensive research to analyze internal and external factors affecting the banks' financial performance and suggests using alternative bankruptcy prediction methods for comparison.